The Transitioning Experiences from Traditional to Agile Project Management: A Case of an Information Technology Department of a Private-Owned Financial Institution in Cebu City - Gerona, Abigail W.; Ocampo, Alex P. (Future Science / FSH-PH Publications, 2023)
Incorporating the Agile Project Management (APM) approach was the institution’s initiative to accelerate project delivery and be more flexible in changing requirements and client demands while producing quality software. The research explores the lived experiences of the institution's project managers to uncover the challenges and demonstrated benefits during Agile Project Management (APM) implementation. This research utilized the qualitative approach through interviews with key informants who are project managers of the institution. The data gathered were from the responses of the five (5) private-owned financial institution project managers. The responses were thoroughly reviewed and tabulated to reveal the commonalities in the data gathered. The study showed that implementing APM significantly changed how the project management team handled and delivered the projects. The project management team moved the project with agility by simplifying the scope and adapting to changes in requirements to increase customer satisfaction and value; the teams were more collaborative, flexible, and able to cope with the risks. However, the study revealed that the main challenges that the project management team experienced were the uncontrollable growth of changes in project scope, under-estimated timelines, and inefficient allocation and delegation of workloads, which resulted in the delayed delivery of projects. Also, it revealed that the current coping strategies were deprioritizing other projects to accommodate new requirements, extending project deadlines, and rendering overtime, which could have been more sustainable when appropriately handled. Furthermore, the study provided recommendations and action plans to improve the implementation of Agile Project Management.